2015
DOI: 10.2147/ott.s79647
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in response to antimetabolites directed at ribonucleotide reductase and thymidylate synthase

Abstract: New agent development, mechanistic understanding, and combinatorial partnerships with known and novel modalities continue to be important in the study of pancreatic cancer and its improved treatment. In this study, known antimetabolite drugs such as gemcitabine (ribonucleotide reductase inhibitor) and 5-fluorouracil (thymidylate synthase inhibitor) were compared with novel members of these two drug families in the treatment of a chemoresistant pancreatic cancer cell line PANC-1. Cellular survival data, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Inhibitors of apoptosis (IAPs) could facilitate cell death, but their expression pattern is decreased in various cancers. In pancreatic cancer, it was confirmed that IAPs are constitutively enhanced by NF-κB in tissues and cell lines ( 75 ). This ectopic overexpression of IAPs is associated with cancer progression and chemotherapy resistance.…”
Section: Exosomes Regulate Therapy Resistance In Pancreatic Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…Inhibitors of apoptosis (IAPs) could facilitate cell death, but their expression pattern is decreased in various cancers. In pancreatic cancer, it was confirmed that IAPs are constitutively enhanced by NF-κB in tissues and cell lines ( 75 ). This ectopic overexpression of IAPs is associated with cancer progression and chemotherapy resistance.…”
Section: Exosomes Regulate Therapy Resistance In Pancreatic Cancermentioning
confidence: 93%
“…Similarly, the expression pattern of IAPs in exosomes exhibited no significant alteration. This stability may partly account for why pancreatic cancer is resistant to chemotherapy ( 75 ).…”
Section: Exosomes Regulate Therapy Resistance In Pancreatic Cancermentioning
confidence: 99%
“…Inhibitor of apoptosis protein (IAP) can promote apoptosis in tumour cells; however, its expression significantly decreases in different types of tumour cells ( 54 ). In a study on PC tissues and cell lines, Asuncion Valenzuela et al ( 107 ) demonstrated that IAP expression is significantly upregulated by nuclear factor-κB. Exosomes derived from PC contain the associated mRNA of IAP, and following chemotherapy, the protein or mRNA IAP levels in the cytoplasm of PC cells remain unchanged or moderately upregulated.…”
Section: Mechanisms By Which Exosomes Promote Pc Metastasismentioning
confidence: 99%